Growth characteristics of ten Mucuna accessions and their effect on speargrass Imperata cylindrica (L.) dry matter - Chikoye, David; Ekeleme, F. (Informa UK Limited, 2001)
Imperata cylindrica (L.) Rauesch. is one of the most common and difficult weeds to control in many crops grown in West Africa. Studies were conducted from 1997 to 1999 in the forest/savannah transition zone to identify growth characteristics that enhance the competitive ability of Mucuna accessions against I. cylindrica. Significant interactions between accession and year were found for all growth characteristics and I. cylindrica dry matter (DM). Seedling density, leaf area index (LAI), percentage ground cover, and DM of Mucuna differed with accession and year (p < 0.05). Accession and year (p < 0.05) also affected I. cylindrica DM. After 3 years, reduction in the DM of I. cylindrica ranged from 58 to 89%, relative to the amount present at the beginning of the study. All growth characteristics of Mucuna were negatively correlated with I. cylindrica DM (r = −0.63 to −0.86, p < 0.05), with LAI being the most important. M. cochinchinensis, M. jaspeada, and M. Veracruz (mottled and white seeded) reduced the DM of I. cylindrica most while M. preta and M. rajada were the least effective.